2011
DOI: 10.1158/0008-5472.can-11-0907
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3 Enhances a T-Cell–Dependent Epidermal Proliferative Response and Promotes Skin Tumorigenesis

Abstract: The chemokine receptor CXCR3 has been proposed to play a critical role in host anti-tumor responses. In this study, we defined CXCR3-expressing immune cell infiltration in human skin squamous cell carcinomas and then used CXCR3 deficient mice to assess the contribution of CXCR3 to skin tumorigenesis. Our studies employed two established protocols for chemical skin carcinogenesis (MCA or DMBA/TPA models). CXCR3 deletion did not affect tumor development in the MCA model; however, CXCR3 was important in the DMBA/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…A recent study showed that the novel chemokine chemerin can recruit NK cells to mediate tumor surveillance (Pachynski et al, 2012), but it remains unclear what induces chemerin during inflammation. The chemokine receptor CXCR3 is expressed on NK cells (Uppaluri et al, 2008) and it ligands ITAC, MIG, and IP-10 can be induced by interferons during tumor development, but this receptor-ligand axis is not involved in the surveillance of MCA-induced sarcomas (Winkler et al, 2011). On the other hand, CXCR3 is thought to be the receptor that mediates the recruitment of cytokine-secreting CD27 high NK cells into lymph nodes (Martin-Fontecha et al, 2004, Watt et al, 2008), and it may be possible that IL-17D can also induce CXCR3 ligands, either directly or indirectly via NK-cell production of IFNγ.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the novel chemokine chemerin can recruit NK cells to mediate tumor surveillance (Pachynski et al, 2012), but it remains unclear what induces chemerin during inflammation. The chemokine receptor CXCR3 is expressed on NK cells (Uppaluri et al, 2008) and it ligands ITAC, MIG, and IP-10 can be induced by interferons during tumor development, but this receptor-ligand axis is not involved in the surveillance of MCA-induced sarcomas (Winkler et al, 2011). On the other hand, CXCR3 is thought to be the receptor that mediates the recruitment of cytokine-secreting CD27 high NK cells into lymph nodes (Martin-Fontecha et al, 2004, Watt et al, 2008), and it may be possible that IL-17D can also induce CXCR3 ligands, either directly or indirectly via NK-cell production of IFNγ.…”
Section: Discussionmentioning
confidence: 99%
“…For example, expression of Cxcr3 in T cells [125] and the receptor for advanced glycation end-products RAGE [126] in immune cells, but not in keratinocytes, was found to be required for sustaining TPA-induced infiltration of inflammatory cells, epidermal hyperplasia and tumor promotion. Analysis of the role of Runx3 has shown that while 100% of DMBA/TPA WT ICR mice developed multiple skin papilloma tumors, the degree of inflammation-associated epithelial hyperplasia and the frequency of papilloma-bearing mice were strongly reduced in Runx3 −/− mice [18].…”
Section: Skin Tumorsmentioning
confidence: 99%
“…Antigen-specific immunity toward mutant Ras or P53 protein fails to eradicate mutant oncogene-expressing epidermal cells and even induces a remarkable enhancement of tumor growth (25,26). T cells can promote papilloma development (21,27,28) and deficiency of CXCR3, an important chemokine receptor for T-cell recruitment, inhibits skin tumorigenesis (29). Antithymocyte serum has no effect on papilloma regression (30).…”
Section: Discussionmentioning
confidence: 99%